The Mystery of Rhomboid in Capicua mutant Fruit Flies - Saleem Hassan, Ali; Nilson , Laura A. (McGill Science Undergraduate Research Journal, 2006)
Drosophila melanogaster is a fruit fly that is one of the most commonly used animal model for genetic studies. Dorsal-ventral (dv) patterning, which is the body plan, of the Drosophila embryo is determined by the asymmetric positioning of different underlying cellular molecules. DV patterning of the Drosophila embryo is established well before fertilisation. The Drosophila egg develop within a cluster of cells consisting of an oocyte interconnected with fifteen sister nurse cells, which function as a source of RNAs and proteins for the developing oocyte and degenerate by the end of oogenesis. Surrounding this cluster is an epithelium of follicle cells, which provide yolk and secrete the eggshell (Fig1). Initial dv asymmetry is established at mid oogenesis and the information is then passed on to the surrounding follicle cells (3). The protein gurken (grk), in the oocyte, provides the initial polarizing signal to initiate the formation of the eventual polarity of the egg, and activates Drosophila epidermal growth factor receptor (EGFR) signaling in the dorsal follicle cells. Through positive and negative feedback mechanisms, this EGF signaling is refined and defines a precise pattern of cell fates within the follicular epithelium (3). This specific definition of fates will be used as a basis to understand the effects of the gene capicua (cic) on follicle cell fate patterning.